Islamic Progressive and Sharia Banking Problems During Covid-19 Pandemic - Trimulato (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2023)
Background: The emergence of the Covid-19 pandemic has caused several sectors to be badly affected. Including sharia banking as an affected institution resulting in decreased performance. In conditions like these, Islamic banks still have to survive to be able to provide the best service and maintain the trustworthiness of customer funds. Objectives: The purpose this study to determine development sharia banking, and progressive Islamic thought for sharia banking problems. Novelty: The concept of Progressive Islamic can be a reference in maintaining stability and protecting Islamic banks from various problems during the Covid-19 pandemic. Research Methodology / Design: The method used this research is field research, using qualitative. The Sources used study are secondary data, from various sources considered relevant research theme. The data analysis technique used research is descriptive qualitative, which describes the development of sharia banking and the role of progressive Islam for sharia banking problems. Findings: This study indicate growth sharia banking during covid-19 pandemic period April 2020 to April 2021. Sharia banking assets grew 13.96 percent, Third Party Funds grew 14.16 percent, financing grew 7.96 percent, income grew 1.43 percent, and non-performing financing grew by 4.83 percent. Sharia banking must be more open to suggestions or responses from various parties as a form of improvement. The input can be sourced from anywhere that is in line with the concept of sharia banking itself. One of them is from progressive Islam itself, which focuses on many things in society. Among them is the focus of progressive Islam, namely on justice, this must be a reference for Islamic banks for their activities. Because justice is also the goal of Islamic economics and following sharia law. Implication: Some of the concepts and values of Islamic progressive can be adopted by sharia banking in overcoming several problems that have arisen due to the Covid-19 pandemic. such as carrying out various product developments and updating services by maximizing technology-based services.